The Value of Preoperative Local Symptoms in Prognosis of Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy: A Retrospective, Multicenter Cohort Study - Yeh, Hsin-Chih; Chang, Chao-Hsiang; Fang, Jen-Kai; Chen, I-Hsuan Alan; Lin, Jen-Tai; Hong, Jian-Hua; Huang, Chao-Yuan; Wang, Shian-Shiang; Chen, Chuan-Shu; Lo, Chi-Wen; Yu, Chih-Chin; Tseng, Jen-Shu; et al. (Frontiers in Oncology, 2022)
Purpose: We aimed to evaluate the impact of preoperative local symptoms on prognosis after radical nephroureterectomy in patients with upper tract urothelial carcinoma (UTUC). Methods: This retrospective study consisted of 2,662 UTUC patients treated at 15 institutions in Taiwan from 1988 to 2019. Clinicopathological data were retrospectively collected for analysis by the Taiwan UTUC Collaboration Group. The Kaplan-Meier method was used to calculate overall survival (OS), cancer-specific survival (CSS), disease-free survival (DFS), and bladder recurrence-free survival (BRFS). The prognostic value of preoperative local symptoms in OS, CSS, DFS, and BRFS was investigated using Cox proportional hazards models. Results: The median follow-up was 36.6 months. Among 2,662 patients, 2,130 (80.0%) presented with hematuria and 398 (15.0%) had symptomatic hydronephrosis at diagnosis. Hematuria was associated with less symptomatic hydronephrosis (p <0.001), more dialysis status (p = 0.027), renal pelvic tumors (p <0.001), and early pathological tumor stage (p = 0.001). Symptomatic hydronephrosis was associated with female patients (p <0.001), less dialysis status (p = 0.001), less bladder cancer history (p <0.001), ureteral tumors (p <0.001), open surgery (p = 0.006), advanced pathological tumor stage (p <0.001), and postoperative chemotherapy (p = 0.029). Kaplan-Meier analysis showed that patients with hematuria or without symptomatic hydronephrosis had significantly higher rates of OS, CSS, and DFS (all p <0.001). Multivariate analysis confirmed that presence of hematuria was independently associated with better OS (HR 0.789, 95% CI 0.661–0.942) and CSS (HR 0.772, 95% CI 0.607–0.980), while symptomatic hydronephrosis was a significant prognostic factor for poorer OS (HR 1.387, 95% CI 1.142–1.683), CSS (HR 1.587, 95% CI 1.229–2.050), and DFS (HR 1.378, 95% CI 1.122–1.693). Conclusions: Preoperative local symptoms were significantly associated with oncological outcomes, whereas symptomatic hydronephrosis and hematuria had opposite prognostic effects. Preoperative symptoms may provide additional information on risk stratification and perioperative treatment selection for patients with UTUC.